Time-related factors predicting a positive response to cardiac resynchronisation therapy in patients with heart failure - Wilczek, Jacek; Jadczyk, Tomasz; Wojakowski, Wojciech; Gołba, Krzysztof S (Scientific reports, 2023)
This study aimed to identify time parameters predicting favourable CRT response. A total of 38 patients with ischemic cardiomyopathy, qualified for CRT implantation, were enrolled in the study. A 15% reduction in indexed end-systolic volume after 6 months was a criterion for a positive response to CRT. We evaluated QRS duration, measured from a standard ECG before and after CRT implantation and obtained from mapping with NOGA XP system (AEMM); and the delay, measured with the implanted device algorithm (DCD) and its change after 6 months (ΔDCD); and selected delay parameters between the left and right ventricles based on AEMM data. A total of 24 patients presented with a positive response to CRT versus 9 non-responders. After CRT implantation, we observed differences between responders and non-responders group in the reduction of QRS duration (31 ms vs. 16 ms), duration of paced QRS (123 ms vs. 142 ms), and the change of ΔDCDMaximum (4.9 ms vs. 0.44 ms) and ΔDCDMean (7.7 ms vs. 0.9 ms). The difference in selected parameters obtained during AEMM in both groups was related to interventricular delay (40.3 ms vs. 18.6 ms). Concerning local activation time and left ventricular activation time, we analysed the delays in individual left ventricular segments. Predominant activation delay of the posterior wall middle segment was associated with a better response to CRT. Some AEMM parameters, paced QRS time of less than 120 ms and reduction of QRS duration greater than 20 ms predict the response to CRT. ΔDCD is associated with favourable electrical and structural remodelling.Clinical trial registration: SUM No. KNW/0022/KB1/17/15.
Keywords: časové faktory; Humans; srdeční resynchronizační terapie; výsledek terapie; Heart Failure; lidé; srdeční selhání; Treatment Outcome; Time Factors; Cardiac Resynchronization Therapy; Electrocardiography; elektrokardiografie